How Does Sense of Agency Develop Across Adolescence? - Slack, Hannah R. (2023)
A sense of agency (SoA) refers to an individual’s awareness of their control over their voluntary actions and the sensory consequences of those actions. Experiencing a veridical SoA is imperative to basic functioning as it facilitates effective goal-directed action. Despite this, a consensus on the trajectory at which the capacity to experience a SoA develops from childhood to adulthood has remained absent from past literature. To resolve this issue, SoA development was investigated by evaluating the influence of age on the functional efficiency of the forward model; the cognitive framework believed to generate a SoA. More specifically, the current research examined the extent to which children, adolescents and adults could, i) accurately predict the outcome of their action, and ii) update their action-outcome knowledge following post-action feedback; two skills indicative of a precise forward model.